2021
DOI: 10.1111/1365-2435.13928
|View full text |Cite
|
Sign up to set email alerts
|

Adequate sample sizes for improved accuracy of thermal trait estimates

Abstract: Thermal traits, such as upper and lower critical thermal limits, are vital indicators of the vulnerability of populations and species to environmental change. Thus, accurate estimates of these traits are needed to explain biological patterns and forecast responses to the changing thermal environment. However, many thermal trait studies measure relatively few individuals to estimate traits for whole populations or species. To ascertain if, and how, sample size affects the accuracy of reported trait means and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…A meta‐analysis of the published experimental data could help delineate the initial and persistent effects of developmental temperatures on thermal tolerance, as well as explaining the heterogeneity across studies. For instance, a meta‐analysis may resolve discrepancies between studies by increasing statistical power (Duffy et al, 2021 ) and highlighting potential differences between species based on their ecology, evolutionary history, or differences in experimental methodology (Gurevitch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of the published experimental data could help delineate the initial and persistent effects of developmental temperatures on thermal tolerance, as well as explaining the heterogeneity across studies. For instance, a meta‐analysis may resolve discrepancies between studies by increasing statistical power (Duffy et al, 2021 ) and highlighting potential differences between species based on their ecology, evolutionary history, or differences in experimental methodology (Gurevitch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…As recently demonstrated for Iberian lizards, for example, such variation can range up to 3°C (Herrando-Pérez et al, 2019;Herrando-Pérez et al, 2020), a factor among many others (e.g. sample size, geographical bias, plasticity) that can cause our predictions to either over-or underestimate true conditions (Duffy et al, 2021;Gunderson & Stillman, 2015;Seebacher et al, 2015;White et al, 2021). Thus, our results should not be generalised to all populations of a species, since thermal physiology and microclimatic conditions vary across geographical ranges.…”
Section: Discussionmentioning
confidence: 78%
“…Our approach is based on thermal traits estimated for a single population per species, assuming no intraspecific variation in their thermal phenotypes. Intraspecific variation in CT max , however, can be substantial (Duffy et al, 2021; Herrando‐Pérez et al, 2019; Herrando‐Pérez et al, 2020). As recently demonstrated for Iberian lizards, for example, such variation can range up to 3°C (Herrando‐Pérez et al, 2019; Herrando‐Pérez et al, 2020), a factor among many others (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation suggested that sampling error is likely to make a non-negligible contribution to heterogeneity among estimates of mutational variance (Conradsen et al 2022). Similarly, a recent meta-analysis of population means of thermal physiological limit traits suggested that < 8% of 428 estimates were supported by sufficient sample sizes for the mean to be estimated with a high-level of accuracy (Duffy et al 2021). Thermally dependent traits are likely to remain the focus of understanding how populations can persist under and adapt to changing conditions, but we suggest that the experimental effort involved in obtaining useful and robust parameter estimates is far from trivial, while the risk of inaccurate estimation must also be carefully considered.…”
Section: Discussionmentioning
confidence: 99%